Citra Merek Sebagai Pemediasi Antara Manajemen Kualitas Total dan Kepuasan Pelanggan di Tambak Udang Venambak - Rahmad Efendy; Infensius Gea; Ratna Ashary; Roma Pasaribu; Irwan Sinaga (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the role of brand image as a mediating variable in the relationship between Total Quality Management (TQM) and customer satisfaction at Venambak Shrimp Farm. The background of this study is based on the importance of quality in the competitive aquaculture industry, as well as the need to build a strong brand image to maintain customer satisfaction and loyalty. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Square (SEM-PLS) method as an analysis technique. Data were obtained by distributing closed questionnaires to consumers who had purchased shrimp products from Venambak Shrimp Farm. The analysis was conducted using SmartPLS software. The results of the study indicate that TQM has a positive and significant influence on brand image and customer satisfaction. In addition, brand image is proven to significantly influence customer satisfaction and plays a role as a mediating variable in the relationship between TQM and customer satisfaction. This means that good internal quality not only has a direct impact on satisfaction, but also indirectly through the formation of positive brand perceptions in the minds of consumers. These findings emphasize the importance of quality management strategies integrated with branding strategies in the context of the aquaculture industry. The practical implication of this research is the need for management to not only focus on improving internal processes, but also strengthening brand image in order to be able to create added value and increase customer satisfaction in a sustainable manner.